Aromatic donor–acceptor interaction promoted catalyst assemblies for hydrolytic kinetic resolution of epichlorohydrin. Issue 1 (10th December 2018) - Blechschmidt, Daniel R.; Woodhouse, Matthew D.; Inagaki, Sebastien; Whitfield, Melita; Ogunsanya, Ayokunnumi; Yoder, Aaron; Lilly, Daniel; Heim, Eric W.; Soucie, Luke N.; Liang, Jian; Liu, Yu
Abstract : The catalyst activity of bis-acceptor functionalized Co(iii )–salen in hydrolytic kinetic resolution can be fine-tuned by introducing a proper donor compound. Abstract : Three generations of Co(iii )–salen complexes containing electron-deficient aromatic moieties (acceptors) have been synthesized. When electron-rich aromatic compounds (donors) were introduced, these complexes were designed to form catalyst assemblies through aromatic donor–acceptor interaction. For all three generations of complexes, the addition of a proper donor led to higher catalytic efficiency in the hydrolytic kinetic resolution (HKR) of epichlorohydrin. The reaction rates are in the following order: Generation 3 > Generation 2 > Generation 1. The aromatic donor–acceptor interaction was verified by NMR spectroscopy and UV-vis absorption spectroscopy studies. These results demonstrated that aromatic donor–acceptor interaction can be a valuable driving force in the assembly of supramolecular catalysts.